Environment in the European Union-1995 : report for the review of the fifth environmental action programme. - Wieringa, Keimpe (Office for Official Publications of the European Communities, 1995)
This publication covers the trends, the state and the outlook of the environment in the European Union. It gives an overview of the environmental measures taken to date, analyses the main trends insociety giving rise to pressure on the environment, analyses the different environmental issues and so-called target sectors and includes an assessment of the costs of implementation of environmental measures. The report was requested by the European Commission as part of the review process of the Fifth Environmental Action Programme "Towards Sustainability"; it is an update of the 1992 report on the state of the environment and also contains an environmental assessment of the progress of the Fifth Environmental Action Programme.